FEATURES OF THE FORMATING OF A GLAMOR COSTUME OF 1930 – 1950'S YEARS - Будяк, В. В. (Art and Design, 2018)
To analyze the costumes of Hollywood actresses in the period 1930 – 1950's, which became the basis for the formation of typical structures of a glamor costume in the XX century; to establish the peculiarities of their formation and to determine their place in the structure of a fashionable costume of the beginning of the XXI century. The stylistic and associative methods of studying the artistic compositional features of the glamorous outfit of actresses as a creative source in contemporary design practice have been used, the comparative-historical method and the method of system-comparative analysis have been applied, which allowed to carry out the general typology of structures of a glamor suit of a certain period and to establish the peculiarities of its formation. The research shows how in 1930 – 1950's designers of American film studios developed stylistics of a glamorous suit, focusing on the individual characteristics of the body of the structure and appearance of the actresses, their role in the film industry. The results obtained concerning the structures of costumes of actresses and the peculiarities of their formation make it possible to characterize the artistic and compositional features of a glamorous costume and to show that they became the basis for the formation of typical images, and eventually – the typological structures of a glamor style suit, which before that time remain relevant and practically unchanged in the design of promising forms of clothing in stylistics of glamor. The peculiarities of the formation of a glamor suit in a certain period are established; outlined the formative searches of the designers of the cinema industry in the development of stylistics of glamor, which was reflected, first of all, in the formation of typical costume structures, its silhouette forms, constructive-compositional solution, the application of materials and their decorating; the basic means of embodiment of typical figurative-stylistic and formal-compositional signs of style of glamor in modern design practice are established. The practical significance of the work lies in the fact that the main results of the study may be useful for the development and production of clothing collections in the style of glamor; Provide capacious information on figurative-stylistic and formally-constructive characteristics of the typical glamor style of costume structures, silhouette forms and methods of shaping in general. The results can be used in the professional training of designers in order to improve the quality of design and art solutions in the development of collections of fashionable clothing that meet the aesthetic demands of contemporaries.